PENGOPERASIAN RUMPON ELEKTRONIK PADA ALAT TANGKAP BAGAN DI PULAU LANCANG KEPULAUAN SERIBU JAKARTA - Yusfiandayani, Roza; Jaya, Indra; Baswantara, Arif (Jurnal Teknologi Perikanan dan Kelautan, 2014)
Electronics FADs is an innovative fishing tools tha thave the same function as in the general FADs to attract and collect fish. The trial of electronic FADs was did at liftnet gear, in purpose to see the performance of these tools. Effectiveness of use electronic FADs analysis from catch harvest. Electronic FADs has attractor a light (LED, 5 Watts) and sound (10-1000 Hz, 1-20 kHz and 20-100 kHz) with a voltage source of 12 volt battery. Installation ofelectronic FADs in the trial following the existing catch method in the liftnet. Based on catches, electronic FADs managed to collectan average of 4.60 kg if time installation is an hour, and collect an average of 4.07 kg if time installation is 30 minute. Electronic FADs work well, attractor is able to function through out the trial and managed toc ollectt he fish, but when compared the effective ness of the catch to the liftnet, then the use of electronic FADs in the liftnet is still not effective. Suggestions for improving the effectiveness ofelectronic FAD scatchon the liftnet is increase the intensity and power on light attractor, and deeper study of the sounds frequency which response by fish.